Ascent guidance for air-breathing hypersonic vehicles based on dynamic inversion. (16th May 2017) - Liu, Xing; Liu, Lei; Wang, Yongji
This article presents an adaptive ascent guidance strategy based on dynamic inversion for air-breathing hypersonic vehicles. Since dynamic inversion is effective to deal with nonlinear problems, this method is employed here to design the ascent guidance command. Compared with conventional dynamic inversion, an adaptive scheme is added into the guidance strategy, which significantly improves the robust performance of this method. And the stability analysis is given to prove the convergence of the nonlinear system. Besides, considering the real-world dynamic motions of the vehicle should be aware to calculate the guidance command instead of referring to the nominal model, the least squares algorithm with forgetting factor is adopted in this article to estimate the real thrust acceleration. And the reference trajectory generated online by polynomial fitting shows better adaptation to the change of flight environment and less computation time than other trajectory generation methods. Results of simulation are provided to demonstrate the feasibility and effectiveness of this approach.